PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN HERBALIFE DI SPECIAL CLUB SAMARINDA - Ganis Lasia Dewi Ramadhan (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
The Influence of Service Quality and Brand Image on Herbalife Purchase Decisions at Special Club Samarinda, this study aims to analyze the effect of Service Quality (X1) and Brand Image (X2) on Herbalife Purchase Decisions (Y) at the Special Club Samarinda. Data collection techniques are carried out by observation, interviews, and questionnaires, analysis tools use validity, reliability tests and classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study concluded that the variable Service Quality (X1) and Brand Image (X2) simultaneously had a positive effect on Herbalife Purchasing Decisions at the Samarinda Special Club (Y). The results of this study also show that the brand image variable (X2) partially has a significant effect on Herbalife Purchasing Decisions at the Samarinda Special Club (Y), while the Service Quality variable (X1) partially has no significant effect on Herbalife Purchasing Decisions at Special Club Samarinda (X2). The brand image variable (X2) is the variable with the strongest influence on Herbalife Purchasing Decisions at the Samarinda Special Club. The suggestions given should Herbalife improve service quality and maintain the brand image of its products so that they can always be well accepted by the community.